Usability and Acceptance of an Interactive Tablet-Based Exercise Application: A Mixed Methods Study - Baschung Pfister, Pierrette; Tobler-Ammann, Bernadette; Knols, Ruud H.; de Bruin, Eling D.; de Bie, Rob A. (Frontiers in Digital Health, 2020)
Purpose: To investigate usability and acceptance of a newly developed interactive, tablet-based exercise application (app) and to explore personal opinions of therapists when using this app in the clinical setting. Methods: Twenty participants (10 therapists and 10 inactive healthy adults) tested usability of this app performing different test tasks, using the think aloud method, and rated overall satisfaction with the System Usability Scale and acceptance with a modified Technology Acceptance Model Questionnaire. For a secondary objective, personal opinions of therapists were evaluated with two focus groups, one for team leaders and one for team members. Results: Overall, the app was judged to be usable. Effectiveness varied between 73% and 90%, overall satisfaction between 70.5 and 85.5/100 points and acceptance between 74% and 80%. Team leader and team member focus groups considered the app as providing a great opportunity for therapy extension, especially because of its blended character. Barriers to its implementation were seen in the existing clinical working processes, personal attitudes of therapists and uncertainty of who would cover expenses for this new form of therapy. Some improvements such as using videos instead of photos, the integration of more interactive tools and the possibility to add additional exercises were suggested in both settings. Conclusion: The app showed high acceptance and usability in trainees and therapists, although some ideas for upgrading functions were formulated. Before this app can be used in clinical practice, feasibility of this blended approach should be evaluated in a clinical setting.